NDONESIA NEGARA DEMOKRASI BERKUALITAS RENDAH - Budiatri, Aisah Putri (Jurnal Penelitian Politik, 2011)
Since many countries have experienced changes in regime at the end of the 20th century democracy hasbecome political trend Compared with other countries in Europe Latin America and Asia Indonesia becomesone of the latest countries that run the effort ofdemocratization After 32 years ofauthoritarian regime Indonesiahas run process of democratic transition and consolidation After a decade how does the form of democracy inIndonesia This article aims to review a book entitled Democratization in Post Suharto Indonesia that willanswer the question